Between Truth and Appearance: Medea’s Emotional Manipulation through gnomai - Boscà Cuquerella, Alba (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
This work seeks to examine how Medea uses γνῶμαι to manipulate the perception of her emotions by her interlocutors. The tragic genre, between its audience and its characters, generates a contrast that results in varying knowledge levels, to ultimately lead to a strong sense of tragic irony. These levels can be helpful in analysing the emotional manipulation. This is an important point to examine γνῶμαι and emotions in the context in which they are used, i.e., considering how Medea is presented on scene in terms of emotions, how the other characters perceive Medea, and how γνῶμαι are used for this purpose. I will consider the explicit and implicit information provided by γνῶμαι regarding who pronounces each of them and their interlocutor, as well as, when possible, the purpose for which they are used.